WHETHER RES ARE COMPETITIVE FOR CONVENTIONAL SOURCES? - Wantuch, Agnieszka; Janowski, Mirosław (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
Energy is a key factor in the development of the economy, determines the quality of life now and in the future. Just like in other industries, an important factor is the economy and ecology. In recent years, puts particular emphasis on the production of electricity based on renewable sources (RES). Certainly they are inexhaustible and organic, but if they are indeed more profitable than conventional sources. The aim of this article is to present an analysis of the economic efficiency of different energy sources.